2021
DOI: 10.1055/a-1343-2127
|View full text |Cite
|
Sign up to set email alerts
|

Using a Portable Near-infrared Spectroscopy Device to Estimate The Second Ventilatory Threshold

Abstract: A breakpoint in a portable near-infrared spectroscopy (NIRS) derived deoxygenated haemoglobin (deoxy[Hb]) signal during an incremental VO2max running test has been associated with the second ventilatory threshold (VT2) in healthy participants. Thus, the aim was to examine the association between this breakpoint (NIRS) and VT2 in well-trained runners. Gas exchange and NIRS data were collected during an incremental VO2max running test for 10 well-trained runners. The breakpoint calculated in oxygen saturation (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 27 publications
2
35
0
Order By: Relevance
“…In running it has been shown that the SmO 2 breakpoint is be able to predict VT 2 using 10 well-trained runners (5 men and 5 women) [22]. However, in both studies, a possible limitation was the small sample size, as the authors themselves acknowledge.…”
Section: Accepted Manuscriptmentioning
confidence: 90%
See 1 more Smart Citation
“…In running it has been shown that the SmO 2 breakpoint is be able to predict VT 2 using 10 well-trained runners (5 men and 5 women) [22]. However, in both studies, a possible limitation was the small sample size, as the authors themselves acknowledge.…”
Section: Accepted Manuscriptmentioning
confidence: 90%
“…Previous findings have shown the relationship between the HHb or SmO 2 breakpoint and other parameters such as RCP, CP, VT 2 or MLSS 2 3 5 9 19 22 23 24 25 26 using different devices in cyclists, runners and rowers. Of all these, the Humon Hex device only was used in two studies.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, NIRS devices allow one aspect of the muscle response (SmO 2 ) to be monitored during an exercise protocol. In the literature, the muscular response of SmO 2 using NIRS during other physical exercise protocols has been highlighted, observing a significant correlation with the maximum lactate in steady state and the critical power [32] and the second ventilatory threshold [33], where the use of these devices has been indicated as a contribution in optimizing and managing the physical response of the athlete in endurance exercises [34,35]. However, despite the lack of research in the area of resistance training and SmO 2 , the compilation of information presented in this work may contribute to position NIRS devices as an instrument to be used during muscle strength training as a useful alternative, being functional and low cost during the evaluation and planning of muscle strength protocols, optimizing the prescription and management of physical performance in healthy adults.…”
Section: Discussionmentioning
confidence: 99%
“…New trends in resistance and cardiopulmonary training methods appeal to more individualized regimes with a variety of exercises, stimuli and intensities, which are controlled by incorporating new technologies and monitoring tools. Current training methods are based on new approaches to monitoring exercise intensity (e.g., rate of force development, movement velocity), technical execution (e.g., biomechanics, electromyography), readiness (e.g., heart rate variability) and physiological responses (e.g., ventilation, lactate, core temperature, heart rate, muscle oxygen saturation) while providing biofeedback in real time, ensuring the accomplishment of targeted results [125][126][127][128][129][130]. Likewise, a number of portable devices, wearable tools and apps for physical activity and fitness are emerging, making remote control of the patients' evolution possible [131].…”
Section: The Role Of Advanced Training Methods For Healthmentioning
confidence: 99%